Visualization of tumor-immune interaction - target-specific imaging of S100A8/A9 reveals pre-metastatic niche establishment - Eisenblaetter, M; Flores-Borja, F; Lee, JJ; Wefers, C; Smith, H; Hueting, R; Cooper, MS; Blower, PJ; Patel, D; Rodriguez-Justo, M; Milewicz, H; Vogl, T; et al. (Ivyspring International, 2017)
Background Systemic cancer spread is preceded by the establishment of a permissive microenvironment in the target tissue of metastasis – the premetastatic niche. As crucial players in establishment of the pre-metastatic niche, myeloid derived suppressor cells (MDSC) release S100A8/A9, an exosomal protein that contributes to metastasis, angiogenesis, and immune suppression. We report the application of antibody-based single-photon emission computed tomography (SPECT) for detection of S100A8/A9 in vivo as an imaging marker for pre-metastatic tissue priming. Methods A syngeneic model system for invasive breast cancer with (4T1.2) or without (67NR) the tendency to form lung metastasis was established in BALB/c mice. A SPECT-probe has been generated and tested for visualization of S100A9 release. Tumor-associated changes in numbers and fuction of immune cells in pre-metastatic tissue were evaluated by flow cytometry and confocal microscopy. Results S100A8/A9 imaging reflected MDSC abundance and the establishment of an immunosuppressive environment in pre-metastatic lung tissue (activity 4T1.2 vs. healthy control: 0.95 vs. 0.45 %ID; p<0.001). The S100A8/A9 imaging signal in the pre-metastatic lung correlated with the subsequent metastatic tumor burden in the same organ (r2=0.788; p<0.0001). CCL2 blockade and the consecutive inhibition of premetastatic niche establishment was clearly depicted by S100A9-SPECT (lung activity untreated vs. treated: 2 vs, 1.4 %ID). Conclusion We report S100A8/A9 as a potent imaging biomarker for tumor-mediated immune remodeling with potential applications in basic research and clinical oncology.